Kidney and liver histopathology of sea bass Lates calcarifer infected with black body syndrome-associated bacteria - Nuryati, Sri; Yanti, Mauliza; Rahman; Wahyuwardani , Sutiastuti (Jurnal Akuakultur Indonesia, 2023)
Bacterial isolation was carried out on sea bass Lates calcarifer juvenile with black body syndrome (BBS) and isolates of Pseudomonas stutzeri L01, Vibrio harveyi, Bacillus cereus, Salinicoccus roseus, and Pseudomonas stutzeri L02 were obtained. Microscopic anatomical pathology of each bacterium needs to be done to determine its pathogenicity. This study aims to compare the degree of damage to sea bass juveniles’ liver and kidney organs through histopathological observations due to bacterial infections that cause BBS. The degree of histopathological damage was determined by scoring histopathological changes in the tissue under a microscope with a magnification of 40×10 in five fields of view. The data obtained were analyzed using SPSS 24 software and further tested with Kruskal-Wallis and Post Hoc (Mann Whitney). The results showed that fish liver and kidney organs in all treatments experienced necrosis compared to the control treatment, but not significantly different between bacterial infection treatments. Histopathological observations of kidney and liver organs of sea bass juveniles infected with bacteria that cause BBS show necrosis damage that was classified as normal and mild. Keywords: bacteria, histopathology, Lates calcarifer ABSTRAK Isolasi bakteri telah dilakukan pada benih ikan kakap putih yang mengalami black body syndrome (BBS) dan diperoleh isolat bakteri Pseudomonas stutzeri L01, Vibrio harveyi, Bacillus cereus, Salinicoccus roseus, dan Pseudomonas stutzeri L02. Patologi anatomi mikroskopis dari masing-masing bakteri perlu dilakukan untuk mengevaluasi patogenitasnya. Penelitian ini bertujuan membandingkan tingkat kerusakan organ hati dan ginjal benih ikan kakap putih melalui pengamatan histopatologi akibat infeksi bakteri penyebab BBS. Derajat kerusakan histopatologi ditentukan dengan melakukan skoring perubahan histopatologi jaringan di bawah mikroskop dengan perbesaran 40×10 pada lima lapang pandang. Data dianalisis menggunakan software SPSS 24 dan diuji lanjut dengan Kruskal-Wallis dan Post Hoc (Mann Whitney). Hasil pengamatan menunjukkan bahwa organ hati dan ginjal ikan pada semua perlakuan infeksi mengalami nekrosis dibandingkan dengan perlakuan kontrol, tetapi tidak berbeda nyata antar perlakuan infeksi bakteri. Hasil pengamatan histopatologi organ ginjal dan hati benih ikan kakap putih yang diinfeksi dengan bakteri yang menyebabkan BBS menunjukkan kerusakan nekrosis yang tergolong pada derajat normal dan ringan. Kata kunci: bakteri, histopatologi, kakap putih